Manasik Haji dan Umrah Berbasis Moderasi Beragama - Abdul Basir; Robingun Suyud El Syam (JAKA: Jurnal Analisis Kebijakan Kementerian Agama, 2023)
Indonesia is a very plural country in terms of ethnicity, race and religion, including the origins of the pilgrims and Umrah pilgrims, therefore a manasik model solution is needed that accommodates all orients towards the principle of religious moderation. Articles are findings from a type of literature research with a qualitative approach, then analyzed inductively. The research concludes: that religious moderation-based rituals of pilgrimage can be pursued by the six-way guidance method, including: duties, parenting, knowledge, personal change, brotherhood, and devotional leadership. This path is practiced in a Hajj and Umrah guidance in order to absorb the nine values ​​of religious moderation: the middle, perpendicular and proportional, tolerance, deliberation, pioneering, improvement, anti-violence, and culturally friendly. Keywords: rituals; hajj; umrah; religious moderation.